The efficacy of sustained-release chitosan microspheres containing recombinant human parathyroid hormone on MRONJ - Aysegul ERTEN TAYSI; Erdal CEVHER; Melike SESSEVMEZ; Vakur OLGAC; Nuri MERT TAYSI; Berkem ATALAY (Brazilian Oral Research)
Abstract Treatment of patients with bisphosphonate usage is a significant concern for oral surgeons because it interferes with jaw bone turnover and regeneration. In case of adverse effects manifesting related to bisphosphonate use, oral surgeons are usually treating and keep the patient’s symptoms under control. In this study, we aimed to investigate a new treatment protocol for medication-related osteonecrosis of the jaw (MRONJ). This treatment protocol consisted of administering human parathyroid hormone (hPTH) loaded chitosan microspheres which were prepared by ionotropic gelation method or/and the prepared microspheres were suspended in a poloxamer gel. After in-vitro optimization studies, the efficacy of the chosen formulations was evaluated in-vivo studies. Zoledronic acid was administered daily to forty-eight adult female Sprague-Dawley rats, divided into four experimental groups, at a daily concentration of 0.11 mg/kg over three weeks to induce the MRONJ model. At the end of this period, maxillary left molar teeth were extracted. In the first group, the subjects received no treatment. In the negative control group, poloxamer hydrogel containing empty microspheres were immediately applied to the soft tissues surrounding the extraction socket. The treatment group-1 was treated with local injections of poloxamer hydrogel containing hPTH. The treatment group-2 was treated with a single local injection of poloxamer hydrogel containing hPTH-loaded chitosan microspheres. Both treatment groups received a total of 7 µg of hPTH at the end of the treatment protocol. Our study demonstrates successful attenuation of MRONJ through a local drug delivery system combined with hPTH, as opposed to previously attempted treatment strategies.